The effect of Timming and Dosage of Kiambang Bokashi (Salvinia molesta) on the Growth and Yield Shallots (Allium ascalonicum) in Polibag - Rahma, Anisa; Mulatsih, Sri; Rustianti, Sri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
The research aims to determine the effect of the timing of application and the dosage of water hyacinth bokashi, as well as the interaction between the two, on the growth and yield of red onions in polybags. The research uses a Completely Randomized Design (CRD) with 2 factors and 3 replications. The first factor is the timing of bokashi application, which consists of three levels: application at planting time (W0), application one week before planting (W1), and application two weeks before planting (W2). The second factor is the dosage of bokashi, which consists of five levels: control (DO); 12.5 grams (D1); 25 grams (D3); 37.5 grams (D4); and 50 grams. (D5). The research results indicate that the application timing significantly affects plant height at 6 MST, the number of leaves at 2 MST, and the dry weight of red onions. The bokashi dosage significantly affects plant height at 2 MST, 4 MST, and 6 MST, the number of leaves at 2 MST, and the dry weight of the onions. Meanwhile, the interaction between the timing of application and bokashi dosage significantly affects all observed variables, except for plant height at 2 MST, 6 MST, and dry weight, which show a very significant effect. The application of bokashi two weeks before planting (W2) is the best timing that yields better growth and results for red onions compared to applying it at planting time (W0) and one week before planting (W1). The bokashi dose (D3) of 33.22 gr is the optimal dosage for promoting the growth and yield of red onions.